การกำหนดเส้นทางแบบสโตแคสติกสำหรับยานพาหนะ เพื่อลดการปล่อยก๊าซคาร์บอนไดออกไซด์ - กิ่งกาญจน์ คำสุข (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This research presents a mathematical model for a Vehicle Routing Problem (VRP) which takes CO2 emission into account by considering weight (vehicle and loading weight) and velocity factors (Minimize CO2 model). The objective is to minimize CO2 emission by determining an appropriate routing and comparing the result with Classical VRP which aims to minimize total distance (Minimize Distance model); then, solve the problem with Tabu Seach (TS) Method. This study divided into 3 cases classified by vehicle velocity: 15 – 45 km/hr., 45 – 95 km/hr. and 15 – 95 km/hr. Each case was separated into 12 levels by problem size. The number of vehicles was not fixed. Different velocity ranges produced different CO2 emissions. The highest CO2 emission was found at 45 – 95 km/hr., followed by 15 – 95 km/hr., with the lowest at 15 – 45 km/hr. e.g. solution of 5 stations problem, amount of CO2 emission were 13,485 g., 10,871 g. and 7,054 g. respectively. The solution showed that, although the appropriate route solution from the Minimize CO2 model has longer distance than the appropriate route solution from the Minimize Distance model, CO2 emissions of the Minimize CO2 model was 2.27 % lower, on average. Because of different route sequence affect to the CO2 emission parameter include route constant (αij), velocity (vij) and loading weight (wij).